The genus Bittacus Latreille (Insecta: Mecoptera) in Brazil: key to species, distribution maps, new synonym, and three new species - Machado, Renato Jose Pires; de Mello Mendes, Diego Matheus; Rafael, José Albertino (Zootaxa, 2018)
The Brazilian species of Bittacus Latreille (Mecoptera: Bittacidae) are reviewed and one new synonym is proposed (Thyridates willmanni Collucci & Amorin syn. n. of Bittacus diversinervis Souza Lopes & Mangabeira). Three new species are herein described: Bittacus cruzi sp. n. from Amazonas, Presidente Figueiredo and Manaus, B. ferreirai sp. n. from Bahia, Aracatu and B. varzeanus sp. n. from Amazonas, Tefé, bringing the current number of Bittacus species in Brazil to 18. Illustrations, comments, and distribution maps of each species are presented. An identification key to the Brazilian genera of Mecoptera and Bittacus species is also presented.